The European Dimension of British Planning - Williams, Richard H.; Tewdwr-Jones, Mark (Taylor and Francis, 2002)
The UK government of Tony Blair is committed to fostering a European dimension of planning practice. Significant developments in relation to planning within Europe are occurring. The creation of the European Spatial Development Perspective, the reform of the Structural Funds, and the implementation of programmes to foster trans-national co-operation between governments, will all impact on UK government, and on planning system in particular. Even within the UK, devolution and regionalisation will bring new pressures for overall co-ordination on the issue of European spatial planning. Issues concerning the revisions of the Structural Funds in 2000 and 2006, and funding opportunities for local authorities, are closely connected with the theme of this book. More importantly, it is expected that the link between funding and spatial policy within British planning will become more clearly defined during this period. The European dimension of British planning, as a consequence, may grow significantly over the next few years. The authors tackle four key issues in their discussion of this topic: * British political attitudes to Europeanisation issues * The changing relationships between different arms of the state * The often complex interdependencies between tiers of governance * The rapidly changing definition of British urban and regional planning